Shock resuscitation with acupuncture: case report. Issue 3 (23rd February 2006) - Hsu, C-H; Hua, Y; Jong, G-P; Chao, C-L; Liu, J-Y; Hwang, K-C; Chou, P
Abstract : A 77 year old aboriginal woman in an isolated village became drowsy and shocked. Poor weather conditions delayed the arrival of the medical and support team—the roads had been seriously destroyed by torrential rains and helicopter was the only means for delivering critical medical care and support. While waiting for the arrival of the helicopter, and in the absence of the necessary emergency medical equipment, the patient's condition deteriorated. Administration of persistent emergency acupuncture stimulation for 80 minutes helped maintain the patient's vital signs until successful transfer of the patient to hospital. She recovered without any complications of shock and was discharged six days later.